Exploration of Conflict Management Strategies Implemented by Supervisors in Work Teams - Puspita , Diva Mega; Fung, Eric Fulvian; Rahmawati , Rani; Husaini , Ahmad; Sahrudin , Muh; Yasin, Fatah (Lentera Ilmu Nusantara, 2025)
This study aims to explore conflict management strategies used by supervisors in work teams. Conflict in the team is inevitable, but supervisors' strategies in handling conflicts are the key to creating a conducive work environment. With a qualitative approach, this study explores the direct experience of supervisors in dealing with conflicts between team members. Data was collected through journals and articles that included semi-structured interviews with several supervisors in the private sector. The results showed that supervisors used a collaborative approach and open communication in mitigating conflict, as well as adjusting strategies depending on the context of the conflict situation. This research provides important insights into the role of supervisors in maintaining healthy team dynamics.